Localized Prostate Cancer Therapy: Tumor Microenvironment‐Activated Spermine Hydrogel With Real‐Time Autonomous Fluorescence Sensing - Ho‐Fai Chau; Wing‐Sze Tam; Gengguo Deng; Yik Hoi Yeung; Christine Yim Ping Wong; Ka Lo Cheng; Zhengxiao Liu; Lijia Yao; Yi Wang; Angelo H. All; Chi‐Fai Ng; Jinming Di; et al. (Chemistry – A European Journal, 2026)
ABSTRACT Prostate cancer (PCa) remains a significant clinical challenge, particularly in localized therapy, where unmet medical needs persist for effective and targeted treatments. This study introduces an innovative solution by developing the first responsive spermine (Spm) hydrogel with an autonomous sensing function, designed to advance local therapy for PCa. Our hydrogel effectively loads Spm and releases Spm in the acidic tumor microenvironment (TME), providing a responsive therapeutic platform. Incorporating the di‐lysine‐7‐nitrobenzofurazan (NBD‐KK) dye, which is initially quenched by aggregate formation within the hydrogel, the release of Spm can be monitored in real time. With its autonomous sensing capability within the tumor, re‐administration of the hydrogel can be determined based on real‐time monitoring of Spm release. Notably, in vivo results indicate a safe and effective dosage of 0.53 mg of Spm in the hydrogel for prostate tumor inhibition. This novel approach holds promise for enhancing local therapy in PCa and improving the quality of life for patients.